Identification of frequently consumed commercially prepared ready-to-eat foods and beverages in Bangladesh: Identification of frequently consumed RtE foods (Bioresearch Communications, 2021)
Ready-to-eat processed foods and beverages are eaten without further cooking or processing. These are generally energy-dense and contain a high amount of saturated fat, sodium, and added sugar. The consumption pattern of these foods varies regionally, seasonally, and agewise. The present study aims to identify commercially prepared ready-to-eat processed foods and beverages frequently consumed by different age groups in rural and urban areas of Bangladesh during the month of Ramadan and the non-Ramadan period. In this cross-sectional study, 948 individuals from 480 households in all eight administrative divisions of Bangladesh were interviewed during the month of Ramadan and the Non- Ramadan period. We identified puffed rice, peyaju, chanachur, chips, unbranded ice cream to be the overall highly consumed foods, consumed by 46.3, 40.1, 39.6 38.0, and 33.1 percent respondents, respectively. Consumption of foods other than puffed rice was significantly different across the age groups (p